4 Research on the change of heart rate variability under strong noise stimulation. (March 2019) - Lu, L; Zhuang, HW; Zhang, YL
Abstract : Objective: To investigate the effect of different strong noise stimuli on heart rate variability (HRV) in 5 min. Methods: 120 students aged 19–22 years with no diseases were selected; they had not done strenuous exercise within 24 hours. The subjects were divided into four groups of 30 people. Each group was stimulated by white noise for 5 min as follows: group A 105 dB, group B 100 dB, group C 115 dB, group D was the control group. A 1 hour ambulatory ECG was conducted in the four groups. The 5 min average HR, SDNN, PNN50, HF, LF and VLF were measured or calculated. Results: The levels of SDNN, PNN50, LF and VLF of groups A, B and C were significantly lower than those in the control group, while HR was significantly higher than that in the control group (p<0.05). For PNN50, LF and VLF, group C had the lowest values and group A had the highest values. Conclusion: HRV of people exposed to noise appears blunted significantly, which suggests that long-term and regular exposure to strong noise not only harms the auditory system, but also may result in impairment of cardiac autonomic nerve activity.